2023
DOI: 10.1186/s12935-023-02850-9
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrocurcumin regulates the tumor immune microenvironment to inhibit breast cancer proliferation and metastasis via the CYP1A1/NF-κB signaling pathway

Abstract: The NF-κB signaling pathway is overactivated in tumor cells, and the activation of the NF-κB signaling pathway releases a large number of inflammatory factors, which enhance tumor immunosuppression and promote tumor metastasis. The cytochrome P450 (CYP450) system consists of important metabolic enzymes present in different tissues and progressive tumors, which may lead to changes in the pharmacological action of drugs in inflammatory diseases such as tumors. In this study, the anticancer effect of tetrahydrocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In the CYP450 synthetic pathway, a variety of PUFAs serves as substrates to generate epoxides such as epoxyeicosatrienoic acids (EETs) and HETEs 140 . Among epoxides, EETs have been demonstrated to be associated with several cancers 39,127–129,136–138,153–178 . It has been reported that 14,15‐EET levels are significantly higher in breast cancer than in noncancerous tissue 127 .…”
Section: Effects Of Signaling Fas On Cancer Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the CYP450 synthetic pathway, a variety of PUFAs serves as substrates to generate epoxides such as epoxyeicosatrienoic acids (EETs) and HETEs 140 . Among epoxides, EETs have been demonstrated to be associated with several cancers 39,127–129,136–138,153–178 . It has been reported that 14,15‐EET levels are significantly higher in breast cancer than in noncancerous tissue 127 .…”
Section: Effects Of Signaling Fas On Cancer Cellsmentioning
confidence: 99%
“…For example, high levels of CYP1A1 can be detected in patients with smoking‐induced lung cancer 155 . Furthermore, overexpression of CYP1A1 in breast cancer can eliminate the drug effect of tetrahydrocurcumin 136 . In the meantime, the expression of CYP2J2 is also found to be upregulated in various forms of cancer cell lines, including lung cancer, prostate cancer, and kidney cancer 137 .…”
Section: Effects Of Signaling Fas On Cancer Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that THC has great potential in a variety of diseases, including neurological diseases, cardiovascular system diseases, kidney diseases and cancer. Our research group also conducted a multidimensional evaluation of THC through animal studies and found that THC had potential therapeutic effects in cognitive impairment, 20,21 breast cancer, 22 skin photoaging, 23,24 melanin production, 25 type 2 diabetes, 26,27 colon cancer, 28 high-altitude cerebral oedema. 29 In addition, solid dispersion of THC was prepared, which effectively improved its bioavailability 30 and we further valuated its effect on metabolic syndrome, 31,32 Alzheimer's disease (AD) through animal experiments.…”
Section: Introductionmentioning
confidence: 99%